Nilai Nilai Pendidikan Qana’ah dalam Novel Remaja “Sepatu Dahlan” Karya Khrisna Pabichara: Sebuah Analisis Isi - Muhammad Danial Fitroh; Moh. Sakir; Ali Mutafi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to analyze the values of qana’ah (contentment and gratitude) in the novel Sepatu Dahlan by Khrisna Pabichara. This research employs a qualitative approach with a library research design. Data were collected through documentation techniques by analyzing the novel text and supported by relevant literature on Islamic values, character education, and literary studies. The data were analyzed using descriptive qualitative methods to identify and interpret the representation of qana’ah values portrayed in the main character. The results show that the value of qana’ah is reflected in Dahlan through acceptance of reality with sincerity, self-control over desires, patience in facing hardship, absence of envy, and constant gratitude despite economic limitations. These values are not only formed individually but are also strongly influenced by family education through parental role modeling, moral guidance, and everyday life experiences. Furthermore, the value of qana’ah presented in this novel is highly relevant for adolescents in the digital era, particularly in dealing with FOMO, materialistic tendencies, and consumerist lifestyles. Therefore, Sepatu Dahlan can serve as an effective medium for character education in fostering qana’ah, gratitude, resilience, and moral awareness among the younger generation.